Hubungan Pengetahuan Dan Komunikasi Terhadap Perilaku Pencegahan Triad KRR Pada Kelompok Remaja Di SMK N 3 Kota Bengkulu - Sulastri, Sulastri; Murwati, Murwati; Ningrum, Kartika Murya (Jurnal Multidisiplin Dehasen (MUDE), 2025)
Triad KRR is three basic reproductive health threats that are at risk for adolescents, namely Sexuality, HIV/AIDS and Drugs. Sexuality is everything related to human life as a sexual being, namely emotions, feelings, personality, attitudes related to sexual behavior, sexual relations and sexual orientation. Human Immunodeficiency Virus (HIV) is a virus that weakens the human immune system and AIDS is an abbreviation of Acquired Immuno Deficiency Syndrome, which is a collection of symptoms that arise due to a weakened immune system due to infection with the HIV virus and Napza is an abbreviation of narcotics, alcohol, psychotropics, and other addictive substances. Napza are chemical substances that enter the human body, either orally (through the mouth) inhaled (through the nose) and injected. The purpose of this study was to determine the relationship between knowledge and communication with the prevention behavior of the KKR triad in the adolescent group at SMK N3 Bengkulu City. This research design uses an analytical observational method using a Cross Sectional research design, the sample in this study amounted to 30 people, using accidental sampling techniques and the measuring instrument used was a questionnaire. Data analysis using Chi-square (X²) with a significance level of α 0.05. The results of the univariate analysis showed that more than half of the respondents (53.3%) had good knowledge, more than half of the respondents (70%) had poor communication, and more than half of the respondents (60%) had good KRR triad prevention behavior. The results of the bivariate analysis showed a relationship between knowledge and KRR triad prevention behavior with a p value of 0.00 ≤ 0.05 and there was no relationship between communication and KRR triad prevention behavior with a p value of 0.70> 0.05. Thus, it is expected that SMK N3 Kota can provide information about reproductive health in order to prevent students from falling into the Three Basic Threats of Adolescent Reproductive Health (KRR Triad).